Comparison among different pH values of Rhodamine B solution impregnated into mesoporous silica - Jorge, Juliana; Castro, Gustavo Rocha de [UNESP]; Martines, Marco Antonio Utrera (My University, 2013)
We studied the behavior of different pH values of Rhodamine B solution impregnated into pores of mesoporous silica, through structural characterization techniques, such as scanning electron microscopy and porosity measurements, and spectroscopic characterization techniques, such as infrared and luminescence spectroscopy; in order to applications in luminescence. Because, Rhodamine B is an interesting xanthene dye whose optical properties depend of many factors, dye concentration and pH values. MSU-4 type mesoporous silica has been synthesized with Tween 60 surfactant as directing-structure agent and tetraethyl orthosilicate (Si(OEt)4, TEOS) as silica source. The mesoporous structures doped with dyes are promissory materials for several applications, for example, optical sensors and biomarkers.
Keywords: Biological markers; Xanthenes dye; Photoluminescence; pH effect